Grevillea robusta bibliography - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Grevillea robusta is an Australian tree species much used in agroforestry in the Embu-Meru area of Kenya. Its timber is used for fuelwood, poles, and sawn timber, while its foliage makes bedding material in cattle pens on smallholdings. The foliage...